What's Involved in Caring for Dairy Goats - Christopher Decubellis; Izabella Toledo (EDIS)
The 4-H dairy goat project is an excellent choice for young people who enjoy working with animals. This particular project allows a 4-H member to work with the same animal for an extended period, possibly even years, as both “kids” can grow together. This new 4-page publication, written by Chris DeCubellis and Izabella Toledo, will explore some of the minimum requirements to successfully care for a dairy goat. https://edis.ifas.ufl.edu/4h427